X-shaped slotted patch biomedical implantable antenna for wireless communication networks - Abbasi, Muhammad Inam; Ahmad, Sarosh; Manzoor, Bilal; Naseer, Salman; Santos-Valdivia, Nilton; Ghaffar, Adnan (Hindawi Limited, 2022)
Biomedical implantable antennas have a major role in biomedical telemetry applications. Therefore, a compact-size low-profile implantable antenna working in industrial, scientific, and medical (ISM) band at 915 MHz is presented. The presented antenna is a simple slotted patch fed with a coaxial probe of 50 Ω impedance. The patch consists of four slotted resonators printed on a flexible Roger Duroid RT5880 substrate (εr = 2:2, tan δ = 0:0009) with the standard thickness of 0.254 mm. The complete volume of the designed antenna is 7 mm × 7 mm × 0:254 mm (0:08λg × 0:08λg × 0:003λg). The antenna covers the bandwidth from 800 MHz to 1 GHz (200 MHz) inside skin tissue. A good agreement between the simulation and measurements of the antenna has been obtained. Finally, the specific absorption rate (SAR) values have also been analyzed through simulations as 8.17 W/kg inside skin over 1 g of mass tissue. The proposed SAR values are less than the limit of the Federal Communications Commission (FCC). This antenna is miniaturized and an ideal applicant for applications in biomedical implants